Cardiotrophin‐1 decreases intestinal sugar uptake in mice and in Caco‐2 cells. (7th April 2016) - López‐Yoldi, M.; Castilla‐Madrigal, R.; Lostao, M. P.; Barber, A.; Prieto, J.; Martínez, J. A.; Bustos, M.; Moreno‐Aliaga, M. J.
Abstract: Aim: Cardiotrophin‐1 (CT‐1) is a member of the IL‐6 family of cytokines with a key role in glucose and lipid metabolism. In the current investigation, we examined the in vivo and in vitro effects of CT‐1 treatment on intestinal sugar absorption in different experimental models. Methods: rCT‐1 effects on α ‐Methyl‐D‐glucoside uptake were assessed in everted intestinal rings from wild‐type and CT‐1 −/− mice and in Caco‐2 cells. rCT‐1 actions on SGLT‐1 expression in brush border membrane vesicles and the identification of the potential signalling pathways involved were determined by Western blot. Results: In vivo administration (0.2 mg kg −1 ) of rCT‐1 caused a significant decrease on α ‐Methyl‐D‐glucoside uptake in everted intestinal rings from wild‐type and CT‐1 −/− mice after short‐term and long‐term treatments. Similarly, in vitro treatment (1–50 ng mL −1 ) with rCT‐1 reduced α ‐Methyl‐D‐glucoside uptake in everted intestinal rings. In Caco‐2 cells, rCT‐1 treatment (20 ng mL −1, 1 and 24 h) lowered apical uptake of α ‐Methyl‐D‐glucoside in parallel with a decrease on SGLT‐1 protein expression. rCT‐1 promoted the phosphorylation of STAT‐3 after 5 and 15 min treatment, but inhibited the activation by phosphorylation of AMPK after 30 and 60 min. Interestingly, pre‐treatment with the JAK/STAT inhibitor (AG490) and with the AMPK activator (AICAR) reversed the inhibitory effects of rCT‐1 on α ‐Methyl‐D‐glucoside uptake. AICAR also prevented the inhibition of SGLT‐1 observed in rCT‐1‐treated cells. Conclusions: CT‐1 inhibits intestinal sugar absorption by the reduction of SGLT‐1 levels through the AMPK pathway, which could also contribute to explain the hypoglycaemic and anti‐obesity properties of CT‐1.